2007
DOI: 10.1111/j.1365-2702.2007.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Admission decisions following contact with an emergency mental health assessment and intervention service

Abstract: This study highlights the valuable role of mental health nurses in frontline emergency mental health care in particular mental health nurses skills in conducting a risk assessment in an emergency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 24 publications
8
47
2
Order By: Relevance
“…This is in contrast with evidence from previous studies suggesting that individuals with greater social deprivation are less likely to have positive outcomes 34,35 and more likely to be admitted 18 following contact with CRTs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with evidence from previous studies suggesting that individuals with greater social deprivation are less likely to have positive outcomes 34,35 and more likely to be admitted 18 following contact with CRTs.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to the current findings, Brooker et al 18 found that increasing age was associated with the likelihood of being admitted, while Cotton et al 21 found a greater risk of admission for younger patients both at 8-weeks and 6-months following contact with CRTs. Increased age, as suggested by our findings, may reflect increased chronicity of mental health problems and a greater need for care.…”
Section: Discussionsupporting
confidence: 86%
“…It is true that the reduction in the numbers of beds has led to a rise in the threshold for admission (Brooker et al, 2007). Under these circumstances, the skills required when making an accurate diagnosis and assessment of the personal, social, cultural and medical circumstances that New ways of working in acute inpatient care: a case for change that have led to admission and which will be needed to facilitate discharge, are both sophisticated and complex.…”
Section: Expectations Of a Contemporary Acute Inpatient Facilitymentioning
confidence: 99%
“…Uncooperativeness was also cited as a reason for admission. 32,34 Psychosis was associated with hospitalisation in some work, 28,34 although others found no diagnostic differences, 33,35 with one study 33 also finding no significant differences in demographic variables in those admitted. Overall, research findings have been inconsistent.…”
Section: Clinical Profiles Of Patients Admitted To Hospital Despite Tmentioning
confidence: 93%
“…The most common reason for admission was risk to self. [31][32][33] Brimblecombe and colleagues 31 found that 21.1% of patients taken on by CRTs were later admitted: 53.2% due to risk to self; 11.3% due to risk to others; and 8.1% as carers could not cope. However, another study 34 found those at risk of violence or unintentional self-harm through self-neglect or recklessness were more likely to be admitted than those at risk of 'deliberate' self-harm.…”
Section: Clinical Profiles Of Patients Admitted To Hospital Despite Tmentioning
confidence: 99%